PENERAPAN PERSONNEL DAN CULTURAL CONTROL BERBASIS SPIRITUALITAS UNTUK MENINGKATKAN KINERJA KARYAWAN HOTEL F DI SURABAYA - Fifi Nella Kwelianto; Wiyono Pontjoharyo (CALYPTRA, 2018)
This research describes the impact resulting from the implementation of management control system, especially personnel and cultural control based on spiritualityon employee performance. In this study use hotel F located in Surabaya. This research uses qualitative approach with several data searching method that is interview, observation and document analysis, conducted for 4 months from August to November 2017. The results of this study indicate that with the value of spirituality in personnel and cultural control can give a positive impact on the performance of employees and business entities themselves. In this study also explains the recommendations that can beused by business entities to overcome the advantages and weaknesses in applying personnel and cultural control through the addition of values based on the spirituality of personnel and cultural control applied by business entities.